2019
DOI: 10.3892/ol.2019.10198
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitizing effect of 5‑aminolevulinic acid in colorectal cancer in�vitro and in�vivo

Abstract: The radiosensitizing effect of 5-aminolevulinic acid (5-ALA) has been demonstrated in glioma and melanoma in a number of studies. Enhancing the radiosensitivity of colorectal cancer may improve survival rates and lessen adverse effects. The present study assessed the radiosensitizing effect of 5-ALA in colorectal cancer using the human colon cancer cell line HT29 in vitro and in vivo . In vitro , cells were pretreated with 5-ALA and exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 44 publications
(70 reference statements)
1
14
0
Order By: Relevance
“…A series of studies on the combination treatment of 5-ALA and ionizing radiation has been conducted by some research groups, and 5-ALA with subsequent intracellular PpIX accumulation has been found to increase kilo electron volt (KeV) or mega electron volt (MeV) irradiation cytotoxicity in a variety of contexts using mouse models of melanoma, glioma, colon cancer, etc. [5][6][7][8][9][10][11][12][13][14][15]. PpIX expression enhances ROS generation, which increases cellular DNA damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of studies on the combination treatment of 5-ALA and ionizing radiation has been conducted by some research groups, and 5-ALA with subsequent intracellular PpIX accumulation has been found to increase kilo electron volt (KeV) or mega electron volt (MeV) irradiation cytotoxicity in a variety of contexts using mouse models of melanoma, glioma, colon cancer, etc. [5][6][7][8][9][10][11][12][13][14][15]. PpIX expression enhances ROS generation, which increases cellular DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…The total clinical radiation dose is limited to a threshold value to avoid causing any damage to normal cells [3,4]. To overcome this issue, a series of studies on the combination treatment of 5-aminolevulinic acid (5-ALA) and ionizing radiation have been conducted by some research groups using mouse models of melanoma, glioma, and colon cancer [5][6][7][8][9][10][11][12][13][14][15]. It is known that 5-ALA administration specifically results in the accumulation of protoporphyrin IX (PpIX) in cancer cells by inhibiting the conversion PpIX to heme [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Malignant cell radiosensitization by selective 5-ALA uptake was also seen in preclinical models of cancers other than glioma, for example, colon, melanoma, and prostate [22,24,26]. This radiosensitization is thought to occur through mitochondrial damage mediated by PpIX, a metabolic product of 5-ALA that captures light or keV or MeV photons and transfers the energy to O 2 to then generate singlet oxygen.…”
Section: -Ala Enhances Kev and Mev Cytotoxicitymentioning
confidence: 98%
“…Interestingly, 5-ALA with subsequent intracellular PpIX accumulation also increases keV or MeV irradiation cytotoxicity in a variety of contexts [22][23][24][25][26][27][28][29][30][31][32][33]. A robust, detailed physics-based explanation for this is currently lacking, but ample preclinical data attest to the basic mechanism of PpIX interacting with keV photons to generate cytotoxicity greater than the same irradiation given without 5-ALA where 5-ALA serves as a radiosensitizer.…”
Section: -Ala Enhances Kev and Mev Cytotoxicitymentioning
confidence: 99%
See 1 more Smart Citation